An Assessment of Climate Induced Increase in Soil Water Availability for Soil Bacterial Communities Exposed to Long-Term Differential Phosphorus Fertilization - Randall, Kate C.; Brennan, Fiona; Clipson, Nicholas; Creamer, Rachel E.; Griffiths, Bryan S.; Storey, Sean; Doyle, Evelyn (Frontiers in Microbiology, 2020)
The fate of future food productivity depends primarily upon the status of soil health. Interactions between climate change and with the agricultural management of fertilisation are therefore vital to understand. This is particularly relevant for inorganic phosphorus (P) fertilisation, which already suffers from resource and sustainability issues. The soil microbiota are a key indicator of soil health and their functioning is critical to plant productivity. They play an important role in nutrient acquisition, particularly when plant available nutrients are limited. This study assessed the effects of increased soil water availability, differences in inorganic P fertilisation and plant presence in a multifactorial design. Measuring the feedback onto wheat biomass, soil enzymatic activity (dehydrogenase and acid phosphomonoesterase) and soil bacterial community assemblages in a mesocosm experiment. Our results suggest potentially serious consequences for crop productivity and the future health of temperate agricultural soils where rainfall is predicted to increase during autumn and winter as a result of climate change. Results also suggest a heightened sensitivity of bacterial community structure and individual taxa in planted soil to increased soil water availability, with increases in abundance of taxa associated with paddy fields and flooding. This response to elevated soil water availability overrides a long-term sensitivity to inorganic P fertilisation and may have serious economic and environmental consequences, as well as implications for developing sustainable P mobilisation through the use of the soil microbiota in future.